Interventions to improve vaccination coverage of children in hard-to-reach population: A systematic review - Cyntia Puspa Pitaloka; Samsriyaningsih Handayani (International Journal of Public Health Science (IJPHS), 2021)
In the last decade, vaccination has reduced a quarter of child deaths worldwide. Vaccination coverage increased, but the coverage remains low in the hard-to-reach population. We searched articles from Pubmed MEDLINE, SCOPUS, Web of Science, and Science Direct to systematically review interventions to improve children's vaccination coverage in hard-to-reach populations. The expected outcome was vaccination coverage, which mentioned Odds Ratio, mean difference, or difference-in-difference with a 95% CI or p-value. Out of 102 articles identified, five articles from four different countries met the inclusion criteria. Four of the five studies reported a positive impact in increasing vaccination coverage. Interventions that showed good effectiveness in increasing the coverage of childhood immunizations were the application of mHealth given to vaccinators, multiple interventions involving the community, modification of immunization schedules during outreach activities, and immunization screening cards. Despite the inconsistent finding, mHealth with SMS reminders was the most effective intervention to increase vaccination coverage and relatively low-cost. More research was needed in developing a strategic intervention to increase vaccination coverage of children in hard-to-reach populations.